The Single Path: A Novel Breaking The Shackle of Marital Pressure - Jeannette Sharon Kathleene Tengkilisan; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2022)
Marital pressure is one of many cultural problems still existing in Indonesia. Research has shown that Indonesians tend to push individuals to get married as an act of conforming to the cultural dominion. This happens because being unmarried is seen as problematic or uncommon. Worst of all, most Indonesians tend to use the existence of marriage as a standard for value and happiness. This negative belief against unmarried individuals is known as singlism. It includes the act of discriminating, stigmatising, and stereotyping singles. Acknowledging this problem, the writer used the theory of Singlism and the Transactional Theory of Stress and Coping to help create a creative thesis in the form of a satirical novel. This creative thesis aims to show that happiness and value cannot be based on marriage. In the end, this creative thesis managed to show that marriage does not always guarantee happiness and life fulfilment.